2022
DOI: 10.3389/fpsyg.2022.861813
|View full text |Cite
|
Sign up to set email alerts
|

Role of Knowledge Management on the Sustainable Environment: Assessing the Moderating Effect of Innovative Culture

Abstract: Environmental sustainability has become the need of the hour and has been emphasized immensely because of the increased environmental awareness and resulting problems caused due to negligence. This study has intended to determine the role of knowledge management (KM) practices in achieving a sustainable environment with the mediating role of environmental awareness and green technological use. The study further examined the moderating role of green innovative culture between the relationship of KM practices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Tseng et al (2013) observed that cultivating and disseminating green knowledge within firms positively influenced the ideation and execution of creative green solutions, further supporting this notion. GKM cultivates an environment that values and shares green knowledge, thereby fostering innovation and nurturing green culture (Weina and Yanling 2022). Furthermore, GKM equips employees with the necessary tools and knowledge to think creatively about sustainability, enhancing the company's innovative ability to respond to environmental struggles (Abbas and Sağsan, 2019).…”
Section: Development Of Hypothesismentioning
confidence: 99%
“…Tseng et al (2013) observed that cultivating and disseminating green knowledge within firms positively influenced the ideation and execution of creative green solutions, further supporting this notion. GKM cultivates an environment that values and shares green knowledge, thereby fostering innovation and nurturing green culture (Weina and Yanling 2022). Furthermore, GKM equips employees with the necessary tools and knowledge to think creatively about sustainability, enhancing the company's innovative ability to respond to environmental struggles (Abbas and Sağsan, 2019).…”
Section: Development Of Hypothesismentioning
confidence: 99%
“…Nonetheless, educators should aim to design and develop T&L activities which promote sustainability awareness among students in HE classrooms. The literature includes studies such as An and Yang (2022) which emphasize the critical role that students' sustainability awareness plays in achieving SD. There is a need for educators to revisit and re-design T&L activities in view of their HEIs' sustainability agendas to educate students about sustainability issues and encourage them to act about it.…”
Section: Micro-level He Classroom Environmentmentioning
confidence: 99%
“…To remove or reduce the barriers to a circular economy (CE), knowledge management can be applied in the ecosystem to incorporate the sustainability dimension (Weina & Yanling, 2022) and the principles of circular early into the product design. This involves the creation, organisation, accumulation and sharing of knowledge among multiple parties and involves actors from both the macro-environment and the interior of the ecosystem.…”
Section: Literature Reviewmentioning
confidence: 99%